15.9k views
5 votes
12. Solve the following expressions:

i. 10(x - 2) – 4(x +1) + 3(x + 6) = 0
ii. 3(x - 1) + 4(2x +1) = 23.
iii. 2{(x + 1) + (x + 2)} = {(x + 3) + (x +4)}
iv.x+4/2+x-3/3=10
v.x-1/4+x+1/3=10
vi.7x/8+3/8=14
PLEASE ANSWER FAST


2 Answers

3 votes

Answer:

A. –1 ≤ x < 3

Explanation:

12. Solve the following expressions: i. 10(x - 2) – 4(x +1) + 3(x + 6) = 0 ii. 3(x-example-1
User SwethaKandikonda
by
6.8k points
6 votes

Answer:

Explanation:

It is 14

User Tien Hoang
by
6.3k points